Inspiring and creative public places : what are the crucial ingredients when developing a successful arts precinct? a Waitakere City, New Zealand case-study : a thesis submitted for the degree of Master of Public Policy at Massey University, New Zealand - Mason, Nicola Michelle (Massey University, 2007)
The Local Government Act 2002 directs New Zealand local authorities to promote the social, economic, environmental and cultural wellbeing of their communities. Together, these elements can produce profound results for local communities, as has been demonstrated through Waitakere City's Eco City commitments and outcomes. As a further step in this holistic journey, Waitakere City Council has committed itself to developing an arts precinct in the heart of the city. This applied thesis has identified how public policy and other factors described through qualitative research can support the development of a successful arts precinct. Internationally, what was found to be successful when developing creative public places was where a mix of sustainable cultural and creative activities and enterprises were co-located and importantly connected with the existing historical, environmental, economic and industrial character and features of the place. In light of this thesis' findings, the New Zealand addendum to this evidence would be to bring local government into the journey at an early phase of planning, and to make explicit the continuous involvement of local communities in their arts precinct's development. Keywords Sustainability, wellbeing, creative, cultural, local government, public space, policy, participation, urban form and design, Waitakere City, Corban Estate, community, connectivity.
Keywords: New Zealand -- Waitakere; Arts facilities -- Planning; City planning